STRATEGI TIONGKOK UNTUK MENJADI KEKUATAN HEGEMONI DI LAUT NATUNA UTARA - Purba, Monita; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research examines about the strategis which China does to ASEAN engaging territorial dispute in North Natuna Sea. The goal of the strategies is to make China become a hegemonic power in North Natuna Sea region. North Natuna Sea has large amount of resources, especially oil and natural gas. That is why China wants to be the hegemonic power in order to have the maritime rights to exploit the sea resources. The strategies examined in this research are military, economic and political strategy. The strategies which examined are not only about the strategies done to ASEAN as an organization, but also to each of ASEAN’s member. China seems to have a special approach to each of ASEAN’s member tu build a strong tie. With their economic power, China increases their corporation and investment with ASEAN. While giving many economic aids, China also strengthen and increase their military power to deter ASEAN. With their military, economic and political strategies, China hopes that ASEAN will not be able to restrict China’s will to develop and exploit the North Natuna Sea. Key Words: North Natuna Sea, hegemony, strategy, territorial dispute, ASEAN